It Will Be All Right in the Morning : Poems - Burns, Michael, 1953- (Book collections on Project MUSE., 1998)
Ln his plain-spoken lyrics and dramatic monologues, Michael Burns digs at the marrow of living. His poems -- in formal and free verse -- are quick, incisive, and always capable of revealing the dark whimsy fate can deal us and the pain of our own actions and inactions.